Pharmacoepidemiological Rationale for the use of Antibacterial Drugs in Community-Acquired Pneumonia in Children of Different Ages (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The increasing prevalence of community-acquired pneumonia (CAP) in pediatric populations poses a significant clinical and public health challenge worldwide. Rational use of antibacterial therapy plays a critical role in improving treatment outcomes while minimizing risks of resistance, adverse drug reactions, and unnecessary costs. This study explores the pharmacoepidemiological foundations for applying antibacterial drugs in children with CAP across different age groups. Through analysis of prescribing trends, efficacy patterns, and safety profiles, the research highlights key determinants of therapeutic choices, evaluates compliance with international and local clinical guidelines, and identifies gaps that contribute to irrational prescribing. The findings underscore the necessity of age-specific approaches, stronger antimicrobial stewardship, and integration of pharmacoepidemiological data into pediatric clinical practice. Pediatric community-acquired pneumonia (CAP) continues to be one of the most pressing problems in global child health, requiring careful evaluation of antibacterial therapy from both clinical and pharmacoepidemiological perspectives. This work focuses on identifying rational foundations for the use of antibacterial agents in children across varying age groups. Emphasis is placed on age-dependent pharmacological considerations, differences in prescribing trends, and the relationship between therapeutic choices and clinical outcomes. Through in-depth analysis of treatment results and monitoring of drug utilization, the study demonstrates the necessity of evidence-based prescribing practices, highlights inappropriate therapeutic approaches, and underscores the value of pharmacoepidemiological monitoring in optimizing pediatric care. The findings provide insights into rational drug selection, dosage determination, and treatment duration while aligning pediatric therapy with the goals of safety, efficacy, and resistance prevention.